Associations of high HDL cholesterol level with all-cause mortality in patients with heart failure complicating coronary heart disease. Issue 28 (July 2016) - Cai, Anping; Li, Xida; Zhong, Qi; Li, Minming; Wang, Rui; Liang, Yingcong; Chen, Wenzhong; Huang, Tehui; Li, Xiaohong; Zhou, Yingling; Li, Liwen
Abstract : Abstract: The aim of the present study was to evaluate the association between HDL cholesterol level and all-cause mortality in patients with ejection fraction reduced heart failure (EFrHF) complicating coronary heart disease (CHD). A total of 323 patients were retrospectively recruited. Patients were divided into low and high HDL cholesterol groups. Between-group differences and associations between HDL cholesterol level and all-cause mortality were assessed. Patients in the high HDL cholesterol group had higher HDL cholesterol level and other lipid components ( P <0.05 for all comparison). Lower levels of alanine aminotransferase (ALT), high-sensitivity C-reactive protein (Hs-CRP), and higher albumin (ALB) level were observed in the high HDL cholesterol group ( P <0.05 for all comparison). Although left ventricular ejection fraction (LVEF) were comparable (28.8 ± 4.5% vs 28.4 ± 4.6%, P = 0.358), mean mortality rate in the high HDL cholesterol group was significantly lower (43.5% vs 59.1%, P = 0.007). HDL cholesterol level was positively correlated with ALB level, while inversely correlated with ALT, Hs-CRP, and NYHA classification. Logistic regression analysis revealed that after extensively adjusted for confounding variates, HDL cholesterol level remained significantly associated with all-cause mortality although the magnitude of association was gradually attenuated with odds ratio of 0.007 (95% confidence interval 0.001–0.327, P = 0.012). Higher HDL cholesterol level is associated with better survival in patients with EFrHF complicating CHD, and future studies are necessary to demonstrate whether increasing HDL cholesterol level will confer survival benefit in these populations of patients.